Phytoestrogenic Activity of Fresh Bitter Melon (Momordica charantia L.) Fruit Extract on Ovarian Folliculogenesis in Female Mice - Rasyida Ulfa; Nabilah Putroe Agung; Rizky Fitriana; Ali Makmur; Nabila Latifa Hafizsha (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Momordica charantia L., commonly known as bitter melon, is a medicinal plant that contains various bioactive compounds such as flavonoids, saponins, tannins, triterpenoids, and alkaloids. These compounds have potential antifertility properties. This study aimed to evaluate the potential of bitter melon extract as an antifertility agent in female animals. A total of 18 female mice (Mus musculus L.) were divided into three groups: a control group (K0), treatment group 1 (P1) received 5% bitter melon extract, and treatment group 2 (P2) received 10% extract. The mice (Mus musculus L.) were orally administered the extract for 16 consecutive days using the gavage method. On the final day of treatment, the mice were dissected to isolate the ovaries. The ovaries were weighed and processed for histological examination using the paraffin method and Hematoxylin-Eosin staining. The observed parameters included the number of primary, secondary, tertiary, and Graafian follicles. Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s post hoc test to determine statistical differences among groups. The results showed that administration of 5% bitter melon extract significantly increased the number of primary and secondary follicles. However, at the 10% concentration, a reduction was observed in the number of all follicle types, including Graafian follicles. These findings indicate that low-dose bitter melon extract may promote ovarian follicle development, whereas high-dose administration exhibits antifertility potential through a phytoestrogen mechanism that inhibits follicular maturation.